WARAK KERURON: Upacara bagi Mereka yang Mengalami Keguguran - Atmaja, I Gusti Ngurah; Donder, I Ketut; Sena, I Gusti Made Widya (Universitas Hindu Negeri I Gusti Bagus Sugriwa Denpasar, 2024)
The Warak Keuron ceremony is a ceremony that has only been implemented since the 1970s. Before the 1970s, Hindus in Bali did not really question miscarriages. Miscarriage is considered a normal phenomenon that does not need to be held a special ceremony, because it is considered non-fatiguing. However, as time goes by, it turns out that many women after experiencing a miscarriage experience various problems, psychological disorders, trauma, even hallucinations and other difficulties. According to sacred Hindu literature, miscarriage is an event that causes sadness/fatigue both in the person experiencing it and in their environment. So to get rid of it, a ceremony called the Warak Karuron Ceremony needs to be held. The aim is to eliminate pain/fatigue for the mother, so that she does not continue to experience psychological disorders which have very broad impacts. And also to free the baby's spirit which is still trapped in its prakerti body, for this reason its prakerti elements consisting of the Panca Maha Bhuta elements are returned to their origin, the baby's spirit is purified so that it can continue its journey to the sunialoka realm.